In Silico ADME And Molecular Docking Studies of New Thiazolyl-bipyrazole, Pyrazolopyridine and Pyrano[2,3-d]pyrazolopyridine Derivatives as Antibacterial Agents - Metwally, Heba M.; Abdel-Latif, Ehab; El-Rayyes, Ali (Current Organic Chemistry, 2024)
In this study, a series of novel pyrazole-based compounds were synthesized starting from the precursor ethyl 3-(4-amino-1-phenyl-3-((4-sulfamoylphenyl)carbamoyl)-1Hpyrazol- 5-yl)-3-oxopropanoate (2). Various synthetic routes were used to obtain pyrazolylpyrazolone 3, tricyclic dipyrazolopyridine 4a-c, thiazolyl-bipyrazoles 5 & 6, pyrazolo[4,3- b]pyridines 7 & 9, and tricyclic pyranopyrazolopyridine 10a-c. These compounds were screened for their antibacterial activity against four bacterial strains. The promising candidates 4a, 4b, 4c, 7, 9, and 10c exhibited minimum inhibitory concentrations ranging from 0.98 to 31.25 μg/mL. The in silico ADME properties for the active compounds exhibited similar physiochemical properties, with compound 9 demonstrating the best likeness and no inhibition effect on the popular drug metabolism enzyme CYP. Molecular docking simulations highlighted compounds 9 and 10c as potent antibacterial agents via DNA-gyrase inhibition
Keywords: pharmacological activity